FSSR lecturers share passion in art at ILHAM Show 2019 / Mahizan Hijaz Mohammad - Mohammad, Mahizan Hijaz (Corporate Communication Unit, Universiti Teknologi MARA, Perak Branch, 2019)
A group of lecturers from the Faculty of Art and Design (FSSR), UiTM Perak Branch, had been selected to exhibit their artworks at Galeri Prima, Balai Berita, New Straits Time Press (NSTP) Kuala Lumpur. Titled as "ILHAM", it showcased 50 artworks from artists and academicians for public viewing from April 7, 2019 till May 7,2019.